Rethinking the Global South beyond Cartesian dualism: the emergence of environmental awareness - Diego Crescentino; Sergio Caballero (Revista CIDOB d'Afers Internacionals)
Over the past few decades, the concept of the Global South has undergone a remarkable transformation, revealing a disconnect between its geopolitical dimension and its identity of resistance and resilience. This paper tracks the historical development of the concept to address the Cartesian dualism existing at present. To this end, it adopts a qualitative analysis methodology starting from a general theoretical and conceptual review to arrive at a specific agenda: the environment. This agenda enables an empirical examination of the tension between two conflicting models: extractivism, related to geopolitical dynamics; and resistance, linked to the defence of territories and communities. The paper ends with critical reflections on the manipulation of the concept of the Global South and its epistemic co-option, while opening lines of research for the future.